Global Attention to Monkeypox - Kumari , Yollugari Aruna; Reddy , Kanala Somasekhar; Chidrawar , Vijay R.; Gowtham , Annadurai; Varalakshmi, Onamala (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Monkeypox is brought on by a pox virus that is closely linked to the smallpox virus and is spread by intimate contact between humans and animals. When people come into contact with sick animals, they may unintentionally contract the monkeypox. Smallpox vaccinations cross-protect against MPXV due to antigenic similarities. Fever, headache, muscle aches, lymphadenopathy, and a recognisable rash that later develops into papules, vesicles, and pustules that scab over and recover are all signs of monkeypox (MPX). There are now two vaccines on the market: JYNNEOSTM (live, replication incompetent vaccinia virus) and ACAM2000® (live, replication competent vaccinia virus). Antivirals (such as tecovirimat, brincidofovir, and cidofovir) and vaccinia immune globulin intravenous (VIGIV) are available as therapies for monkeypox, albeit the majority of cases will have moderate and self-limited disease and supportive care is often sufficient. The ongoing outbreak, which has more than 10,000 cases in more than 50 nations between May and July 2022, illustrates how easily MPXV can spread among people and how this could pose a serious threat to public health with worldwide repercussions.